Woodburn Grange: A story of English country life; vol. 1 of 3 - Howitt, William, 1792-1879 (Salt Lake City, UT : Project Gutenberg, 2022)
"Woodburn Grange: A Story of English Country Life; vol. 1 of 3" by William Howitt is a novel written in the late 19th century. The story appears to revolve around the last member of the Rockville lineage, Sir Roger Rockville, exploring themes of aristocratic decay and social change within the English countryside. Other characters introduced in the opening portions include the widowed Mrs. Deg and her son Simon, representing a new line against the backdrop of traditional gentry, suggesting a contrast between the established aristocracy and the emerging middle class. At the start of the narrative, we learn about Sir Roger Rockville, the last of a long line of a once-prominent family that has since declined into stagnation. Described as lonely and unable to connect with the changing society around him, Sir Roger's estate is juxtaposed with the rising manufacturing town of Great Castleborough, which represents a shift in social dynamics. Other elements introduced include the character of Simon Deg, a previously destitute individual who is now gaining prominence, setting the stage for a clash between the old order of landed gentry and the new social realities. The opening chapters thus establish a rich array of characters and themes that promise an insightful exploration of class and community in rural England. (This is an automatically generated summary.)
Release date is 2022-12-26
Sonya Schermann, Bob Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Religious fiction